2020
DOI: 10.9734/mrji/2020/v30i1130278
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance Pattern of Staphylococcus aureus and Associated Risk Factors in the Adamaoua and Far North Regions of Cameroon

Abstract: Background: Infections due to Staphylococcus aureus (S. aureus) have been recognized as an important public health problem worldwide. Resistant S. aureus strains emerged and its prevalence has been on the rise. Many risk factors were identified as comorbidities and impact seriously the health state of infected individual by resistant Staphylococcus aureus. We focus our study on two of these risk factors (HIV-infection and diabetes) which may constitute high potential health conditions for emergence of resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Moreover, in our study, pus recorded the highest cases of resistance, similar to Dilnessa's findings in Ethiopia (2016) [35] and Wangai in Kenya (2019) [6]. We suggest that the observed resistance of Staphylococcus aureus might be due to the selection pressure resulting from years of exposure to antibiotics used to kill germs in routine hospital sanitization which was responsible of high rate of multiresistant S. aureus observed in this same area (53.2%) [28]. In our questionnaire, participant information about antibiotic consumption right before sample collection was noted.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, in our study, pus recorded the highest cases of resistance, similar to Dilnessa's findings in Ethiopia (2016) [35] and Wangai in Kenya (2019) [6]. We suggest that the observed resistance of Staphylococcus aureus might be due to the selection pressure resulting from years of exposure to antibiotics used to kill germs in routine hospital sanitization which was responsible of high rate of multiresistant S. aureus observed in this same area (53.2%) [28]. In our questionnaire, participant information about antibiotic consumption right before sample collection was noted.…”
Section: Discussionsupporting
confidence: 86%
“…Previous investigations in North Cameroon region showed: an important antibiotics misuse in human and livestock for Staphyloccocci infections [27] and a high frequency of multiresistant S. aureus. (53,2%) were reported [28]. Besides, few studies in Cameroon have been conducted to assess the problem of S. aureus resistance to penicillin which is the first line prescribe antibiotic when S. aureus infection is diagnosed [29].…”
Section: Introductionmentioning
confidence: 99%
“…[9] and Mohamadou et al [28] obtained greater MRSA prevalence of 58.62% and 51.5% respectively in Yaoundé and in the Adamawa and Far North regions of Cameroon. This difference could be justified by the sample size, which was larger in their studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, Tigist et al [11] and Mendem et al [4] observed increased resistance of S. aureus to penicillin of 95.5% and 97.5% respectively. Other studies have reported considerable resistance to Erythromycin and Ampicillin [33] or Rifampicin and Cotrimoxazole [28]. This variability in resistance to a wide range of antibiotics reveals the limited possibilities and therapeutic choices applicable in emergency circumstances or in a syndromic approach in facilities with limited resources.…”
Section: Discussionmentioning
confidence: 99%